From Ethnic Herbal Medicine to Unani Traditions: Medicinal Plant Knowledge across Southwestern China and Northern Pakistan - Gao Jian; Xu Ziheng; Qu Qiumei (Pakistan Journal of Medical Sciences, 2026)
Ethnic herbal medicine originated from the medical knowledge accumulated by ethnic groups in their struggle against disease and harsh environments; the history of each ethnic group’s development through long-term coexistence and competition with nature is, in itself, a history of medicine. In northern Pakistan, herbal plants thrive and are readily available, and medicinal plants exhibit an exceptionally rich biodiversity. Yunnan’s unique natural environment and biodiversity have fostered a wealth of ethnic medicine and cultural resources, making it a treasure trove of global medicine and culture. There is significant potential for cooperation between Yunnan’s border ethnic regions and northern Pakistan in areas such as pharmaceutical research and development, joint construction of pharmaceutical plants, training of medical professionals, and the exchange of medicinal plant cultivation techniques. This topic was chosen to explore the similarities and cultural significance of traditional medicinal plant knowledge between the ethnic herbal medicine systems of Southwestern China and the Unani medical traditions of Northern Pakistan.